Temperature amplifies the effect of high CO2 on the photosynthesis, respiration, and calcification of the coralline algae Phymatolithon lusitanicum. Issue 19 (13th September 2019) - Sordo, Laura; Santos, Rui; Barrote, Isabel; Silva, João
Abstract: The combination of ocean acidification (OA) and global warming is expected to have a significant effect on the diversity and functioning of marine ecosystems, particularly on calcifying algae such as rhodoliths (maërl) that form extensive beds worldwide, from polar to tropical regions. In addition, the increasing frequency of extreme events, such as heat waves, threatens coastal ecosystems and may affect their capacity to fix blue carbon. The few studies where the simultaneous effects of both temperature and CO2 were investigated have revealed contradictory results. To assess the effect that high temperature spells can have on the maërl beds under OA, we tested the short‐time effects of temperature and CO2 on the net photosynthesis, respiration, and calcification of the recently described species Phymatolithon lusitanicum, the most common maërl species of southern Portugal. Photosynthesis, calcification, and respiration increased with temperature, and the differences among treatments were enhanced under high CO2 . We found that in the short term, the metabolic rates of Phymatolithon lusitanicum will increase with CO2 and temperature as will the coupling between calcification and photosynthesis. However, under high CO2, this coupling will favor photosynthesis over calcification, which, in the long term, can have a negative effect on the blue carbon fixing capacity of the maërl beds from southern Portugal. Abstract : In a short term, the effect of increasing CO2 on the metabolic rates of Phymatolithon lusitanicum will be accentuated with increasing temperature.